2012
DOI: 10.1016/j.biombioe.2012.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of slagging and fouling tendency during biomass co-firing with coal in a fluidized bed

Abstract: Slagging FoulingCo-firing Biomass Fluidized bed a b s t r a c tOver the last decades, several indices based on ash chemistry and ash fusibility have been used to predict the ash behaviour during coal combustion, namely, its tendency for slagging and fouling. However, due to the physicalechemical differences between coals and biomass, in this work only the applicability of an ash fusibility index (AFI) to the combustion and co-combustion of three types of biomass (straw pellets, olive cake and wood pellets) wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
96
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 177 publications
(98 citation statements)
references
References 19 publications
0
96
0
2
Order By: Relevance
“…So far, the researchers have put forward several slagging and fouling indices to predict the ash behavior during coal combustion process, but previous studies (Pronobis 2005;Teixeira et al 2012) reported that there is a lack of specific indices for evaluation of slagging and fouling tendency during biomass combustion process. Hence, in this study, the slagging and fouling tendency of biomass ash was evaluated according to the empirical indices for predicting the coal ash behavior during coal combustion.…”
Section: Slagging and Fouling Characteristics Of Biomass Ashmentioning
confidence: 99%
See 2 more Smart Citations
“…So far, the researchers have put forward several slagging and fouling indices to predict the ash behavior during coal combustion process, but previous studies (Pronobis 2005;Teixeira et al 2012) reported that there is a lack of specific indices for evaluation of slagging and fouling tendency during biomass combustion process. Hence, in this study, the slagging and fouling tendency of biomass ash was evaluated according to the empirical indices for predicting the coal ash behavior during coal combustion.…”
Section: Slagging and Fouling Characteristics Of Biomass Ashmentioning
confidence: 99%
“…The index Rb/a is defined as the base (Fe2O3, CaO, MgO, K2O, Na2O) to acid (SiO2, TiO2, Al2O3) ratio shown in Eq. 4 (Teixeira et al 2012), and this ratio is a mass ratio. Besides, the formulas of these indices that indicate the ash slagging and fouling tendency were also presented in the following Eqs.…”
Section: Slagging and Fouling Characteristics Of Biomass Ashmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of these problems, there is a loss of efficiency due to the reduction of the heat exchange, which results in an increase in the operational and maintenance costs. Therefore, fouling, slagging and corrosion are the main challenges faced by biomass combustion boilers, which are a subject of study for many researchers [4][5][6][8][9][10][11][12][13][14]. The main cause of the formation of these deposits resides in the chemical composition of the biomass used in the combustion.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of high amounts of alkali metals such as K and Na, and large quantities of Cl, S and Si are primarily responsible for these problems. [6,7,9,12,[14][15][16][17][18]. Many researches have focused on minimizing or removing these problems using methods such as co-firing with other types of fuel, such as different coals [9][10][11]13,[19][20][21] or blends of various biomass species [14,22], and the use of additives such as phosphoric acid [3], ammonium sulfate [19], kaolin [14], halloysite [23], titanium oxide [24], Ca-based additives [25] and others [26][27][28].…”
Section: Introductionmentioning
confidence: 99%